Family Coping Strategies During Finland’s COVID-19 Lockdown - Milla Salin; Anniina Kaittila; Mia Hakovirta; Mari Anttila (MDPI, 2022)
During spring 2020, the COVID-19 pandemic and global lockdowns fundamentally changed families’ everyday lives. This study aims to examine how families with children coped during the COVID-19 lockdown in Finland and what kind of coping strategies they developed. An online survey including both qualitative and quantitative questions was conducted between April and May 2020 to gather Finnish families’ experiences during the COVID-19 lockdown. In this study, we focus on information from one open-ended question, and Huston’s social-ecological theory was used as an analytical framework. The results showed that Finnish families employed coping strategies on three levels: macroenvironmental, relationship, and individual. This supports the argument that to better understand families’ coping strategies, the macrosocietal environment surrounding families, their relationships, and the interactions between family members, as well as individual decisions and attitudes, should be taken into account.